Federated Corporate Social Responsibility: Constraining the Responsible Corporation - Caulfield, Matthew; Lynn, Andrew (Academy of Management Review, 2024)
Building from recent criticisms that mainstream political corporate social responsibility has failed to effectively address the potential expansion of corporate influence in society, we advance a new conceptualization of corporate social responsibility inspired by U.S. federalist political theory. As federalism has served as a prevailing U.S. theory for arranging governmental political power for the advancement of the public interest, we derive from federalist principles descriptive, normative, and instrumental theoretical foundations for arranging corporate power and directing corporate social action in the pursuit of similar goals. What we call “federated corporate social responsibility” (FCSR) revives an older institutional approach to corporate responsibility, paying particular attention to the division of moral labor in society and how different corporate responsibility prescriptions stand to affect the social ecosystem of power. Federalist institutional strategies deploying separations of power and constitutions are used to develop a concept of corporate “constitutional devices,” which have promise to constrain the corporation as it fulfills its social responsibilities, even outside the ambit of a strong state and in light of barriers to constant, effective stakeholder accountability. We conclude by outlining FCSR managerial strategies, which sometimes endorse corporate social inaction in the interest of a desirable distribution of authority across society.